Effects of %FIMA on storage-safety parameters of spent fuel from experimental pebble-bed reactor - Aisyah Aisyah; Mirawaty Mirawaty; Saputra, Dwi Luhur Ibnu; Setiawan, Risdiyana; Artian, Pungky Ayu; Ratiko Ratiko; Nasruddin Nasruddin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The back end of the utilization of nuclear technology is safety and management of spent fuel, which is a key element contributing to the success of the nuclear power plant program. Indonesia’s National Nuclear Energy Agency resolved to establish an experimental power reactor, called RDE, as a nuclear power plant demo. The fuel of this reactor is similar to that of German’s experimental pebble-bed reactor (PBR), Arbeitsgemeinschaft Versuchsreaktor(AVR). In this study, the spent fuel of AVR was studied to obtain the safety parameter data for storage of RDE spent fuel by varying the fission in the initial metallic atoms (%FIMA). These parameters that must be studied include the radioactivity, decay heat, proliferation threats of both 239Pu and 235U, and the presence of 137Cs, a dangerous fission product that can escape from damaged spent fuels. The calculation was conducted by ORIGEN 2.1. The result of the study demonstrates a higher %FIMA indicates a higher safety level that is required since the activity and decay heat of the spent fuel will increase and, as will be the total amounts of 239Pu and 137Cs. However, the 235U amount will decrease. For a 100 years storage of spent fuel, the optimum %FIMA is 8.2 with a canister capacity of 1,900 pebbles. Further, the activity and decay heat of the spent nuclear fuel are 2.013 × 1013 Bq and 6.065 W, respectively. The activities of 239Pu, 137Cs, and 235U are 5.187 × 1011, 7.100 × 1012, and 7.339 × 107 Bq, respectively.